Mindfulness-based stress reduction for medical students: a narrative review - Polle, Emma; Gair, Jane (Canadian Medical Education Journal, 2021)
Background: Medical students are at high risk of depression, distress and burnout, which may adversely affect patient safety. There has been growing interest in mindfulness in medical education to improve medical student well-being. Mindfulness-based stress reduction (MBSR) is a commonly used, standardized format for teaching mindfulness skills. Previous research has suggested that MBSR may be of particular benefit for medical students. This narrative review aims to further investigate the benefits of MBSR for undergraduate medical students. Methods: A search of the literature was performed using MedLine, Embase, ERIC, PSYCInfo, and CINAHL to identify relevant studies. A total of 102 papers were identified with this search. After review and application of inclusion and exclusion criteria, 9 papers were included in the study. Results: MBSR training for medical students was associated with increased measures of psychological well-being and self-compassion, as well as improvements in stress, psychological distress and mood. Evidence for effect on empathy was mixed, and the single paper measuring burnout showed no effect. Two studies identified qualitative themes which provided context for the quantitative results. Conclusions: MBSR benefits medical student well-being and decreases medical student psychological distress and depression.